(untitled) (Revista de Letras Norte@mentos, 2017)
The aim of this paper is to address some keys concepts regarding critical frameworks as far as literacies and language education are concerned. In order to meet such a goal, different approaches to what can be understood as critical will be presented and discussed. The theoretical framework which support discussions will rely on a varied group of scholars, such as Norton and Toohey (2001), Morgan (2004), Freire (2005), Luke (2013, 2014), Mills (2016), Menezes de Souza (2011), Monte Mór (2015), Rocha and Maciel (2015), among others. It is expected that the discussions presented may add to the knowledge already built in the area and to the debate about critical literacy and critical linguistic education.